1977
DOI: 10.3758/bf03329369
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the neural mechanisms of baitshyness in rats

Abstract: The effects on taste aversion learning of lesions in a variety of brain areas known to alter taste avoidance and/or shock avoidance behavior were examined in 72 adult male rats. Bilateral lesions of the medial frontal cortex, orbital or sulcal frontal cortex, cingulate cortex, caudate nucleus. medial thalamus, or hippocampus failed to significantly alter taste aversion learning, while bilateral lesions to the amygdala impaired this learning. Lesions to the septum produced equivocal results. There does not appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Perhaps the most striking of these differences is the nature of the UCS employed. For example, four of the five studies that reported no impairment of taste aversion acquisition after large hippocampal lesions (Kolb et al, 1977;Murphy & Brown, 1974;Thomka & Brown, 1975; present study) used LiCl as the US; the fifth (Miller et al, 1975) used cyclophosphamide. On the other hand, two of the three studies reporting an acquisition deficit after hippocampal lesions (Best & Orr, 1973;Krane et al, 1976) used apomorphine as the US; the third (Miller et al, 1971) used X-ray.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Perhaps the most striking of these differences is the nature of the UCS employed. For example, four of the five studies that reported no impairment of taste aversion acquisition after large hippocampal lesions (Kolb et al, 1977;Murphy & Brown, 1974;Thomka & Brown, 1975; present study) used LiCl as the US; the fifth (Miller et al, 1975) used cyclophosphamide. On the other hand, two of the three studies reporting an acquisition deficit after hippocampal lesions (Best & Orr, 1973;Krane et al, 1976) used apomorphine as the US; the third (Miller et al, 1971) used X-ray.…”
Section: Discussionmentioning
confidence: 61%
“…Best and Orr (1973) and Miller et al (1971) had previously reported that hippocampal lesions disrupt taste aversions learned under weak conditioning paradigms that paired a preferred sacch~rin C.S and an apomorphine or X-ray US. At the tlme thls research was conducted, there were no such reports in which LiCI had served as the US, although, in one study that preceded this one, Kolb et al (1977) found a taste aversion deficit in rats with septal lesions when LiCl served both as the US and CS.l This result suggested that under appropriate conditions, septo-hippocampal lesions might disrupt taste .aversions supported by LiCl. The second expenment tested this notion by pairing a preferred sucrose CS with a reduced dose of LiCl as the US.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations